Changes in serum pigment epithelium-derived factor levels after kidney transplantation in patients with end-stage renal disease. Issue 1 (31st December 2022) - Szentimrei, Réka; Lőrincz, Hajnalka; Szentpéteri, Anita; E. Varga, Viktória; Harangi, Mariann; Seres, Ildikó; P. Szabó, Réka; Nemes, Balázs; Paragh, György
Abstract: Background: Pigment epithelium-derived factor (PEDF) is a serin protease inhibitor and a potent inhibitor of angiogenesis. Its serum level has significant associations with metabolic parameters. However, little is known about the association between PEDF levels and lipid parameters in renal transplanted (TX) patients. Therefore, our aim was to investigate the relationship between PEDF level and lipid parameters in TX patients. Methods: Seventy TX patients (47 males, 23 females, mean age 51.7 ± 12.4 years) and 34 healthy controls were enrolled. We examined the serum creatinine, C-reactive protein, fasting glucose and lipid parameters right before, then 1 and 6 months after TX. High-density lipoprotein (HDL)-associated paraoxonase-1 (PON1) activities were measured spectrophotometrically. Lipoprotein subfractions were determined by Lipoprint. PEDF and oxidized low-density liporotein (oxLDL) levels were measured by ELISA. Results: Before transplantation, patients had had a significantly higher PEDF level compared to control subjects ( p  < 0.001). One month after transplantation, their PEDF level decreased significantly reaching the healthy controls' level, and this lower level was maintained during the 6 months follow-up period as well. The initial oxLDL level was significantly higher, while PON1 activities were significantly lower in the patient group compared to the control group. We found a significant positive correlation between PEDF and total cholesterol, low-density lipoprotein (LDL)-cholesterol, triglyceride, oxLDL and small HDL subfraction; while negative correlations were found between PEDF and mean LDL size and large HDL subfraction during the entire follow-up period. Conclusion: PEDF may play an important role in the increased oxidative stress and enhanced atherogenesis in renal transplant patients.